The impact of uncertainty on employment, investment, and output in the Philippines - Cruz, Thea Mariz L. (School of Economics, University of the Philippines Diliman, 2018)
The Real Options Theory of Investment is one of the theories in business and investment that offers explanations as to how uncertainty can influence an investor_s decision on whether or not and when an investment would be made. Nicholas Bloom (2009) finds that uncertainty might also be affecting macroeconomic variables, particularly on employment, investment and output. This study aims to identify moments in Philippine history that can be considered periods of uncertainty. It also determines whether or not there is evidence of the real options theory in Philippines. The study makes use of the Vector Autoregression Model (VAR) to determine the impacts of uncertainty shocks on employment, investment, and output among other macroeconomic variables. It was found that uncertainty does affect multiple macroeconomic variables including the employment, investment, and output in the Philippines and that Philippine firms exercise the real option to delay.